Assessment of acute toxicity of thiamethoxam (Actara® 25WG) to Achatina fulica and its potential ecological applications - Abog, Maria Kim Feliz N.; de Rivera, Jose Jaime Lorenzo C.; Estacio, Sarah Christina W.; Fidelino, Jay S.; Lavilla, Orlie John Y.; Pilapil, John Christopher A.; Tongco, Ma. Dolores C. (Science Diliman: A Journal of Pure and Applied Sciences, 2013)
Achatina fulica is considered as one of the world’s worst invasive species and is known to cause ecological disruption as well as agricultural and health problems in the Philippines. The study evaluated the use of the insecticide thiamethoxam (Actara® 25WG) in the control of A. fulica populations. This was done by performing an acute toxicity test of thiamethoxam to A. fulica . Six individuals each were exposed to thiamethoxam concentrations of 0, 50, 100, 200, and 400 μg/L for 72 hours. The percent mortality was then determined after the exposure period. Probit analysis was used to determine the LD50 of thiamethoxam to A. fulica . The LD50 was found to be 662.95 ± 172.98 μg/L. Using the mean body weight of the snails, the LD50 per body weight of A. fulica was determined to be 90.09 ± 23.60 μg/kg. This is 70 times lower than the recommended application of thiamethoxam on field. Thus, normal application would eliminate A. fulica. However, because the LD50 to A. fulica is higher than that for other beneficial non-target species such as honey bees (0.03 μg/bee), the use of thiamethoxam in the control of A. fulica populations is only recommended when in conjunction with the control of target pest insects.
Keywords: Ecotoxicology, acute toxicity